Health consequences of androgenic anabolic steroid use - Horwitz, H.; Andersen, J. T.; Dalhoff, K. P. (Journal of internal medicine, 2019)
Background The lifetime prevalence of androgenic anabolic steroid abuse is estimated to be around 6% for men, but there is limited knowledge about the side effects of these drugs. Objective To investigate mortality and morbidity amongst users of androgenic anabolic steroids (AAS). Methods In this retrospective matched cohort study, 545 male subjects tested positive for AAS in Danish fitness centres during the period 3 January 2006 to 1 March 2018. Subjects were matched with 5450 male controls. In addition, 644 men who were sanctioned because they refused to submit to a doping test and 6440 controls were included as a replication cohort. Results Mortality was three times higher amongst users of AAS than amongst nonuser controls (hazard ratio 3.0, 95% CI 1.3–7.0). The median annual number of hospital contacts was 0.81 in the cohort of AAS users and 0.36 in the control cohort (P < 0.0001). Acne, gynaecomastia and erectile dysfunction affected more than 10% of the androgenic anabolic steroid users, and the prevalence of these disorders was significantly higher than in the control group (P < 0.0001). The results could be replicated in a similar cohort. Conclusion Androgenic anabolic steroid users have an increased risk of dying and significantly more hospital admissions than their nonuser peers. Side effects of AAS and their metabolites were highly prevalent. Given the high rate of androgenic anabolic steroid abuse, these side effects are of public health concern.